A case of a thoracic mass negative on thoracentesis diagnosed by cryobiopsy from the visceral pleura. Issue 11 (17th October 2022) - Morita, Chie; Kitamura, Atsushi; Kinoshita, Katsuhito; Sueyoshi, Kuniyo; Murakami, Manabu; Ro, Shosei; Imai, Ryosuke; Okafuji, Kohei; Kojima, Fumitsugu; Tomishima, Yutaka; Jinta, Torahiko; Bando, Toru; et al.
Abstract: Thoracoscopy under local anaesthesia is recommended for malignant tumours with negative pleural effusion cytology. Cryobiopsy from the visceral pleura by thoracoscopy under local anaesthesia can provide more diagnostic options for patients with thoracentesis‐negative malignant effusions. Here we present the first case in which this technique was used. The patient had a pleural metastasis that could not be diagnosed even with rapid cytology of the parietal pleura biopsy. Indications, technical pitfalls, and safety tips are discussed. Abstract : Here we report a case of a patient who was negative on thoracentesis and underwent cryobiopsy from the visceral pleura by thoracoscopy under local anaesthesia. The technique was performed safely and led to a diagnosis.